“Una domanda ai compositori” - Ceccarelli, Luigi (Musica/Tecnologia, 2010)
Luigi Ceccarelli takes into account the prerogatives of the current technologies referring to the elements pointed out by the critical commentary of the authors quoted inside the proposed “A question to the composers”. Noting that the remarks are more aimed at certain kinds of use, made to cover a lack of ideas, rather than at technology itself, the author points out how, to make music, a level of complexity of higher “logical standard” should be really reached.